اثر استخدام طريقة الاستجواب في تنمية المفاهيم الإسلامية لدى تلميذات الصف الثالث الابتدائي - م.م. ندى لقمان محمد أمين الحبار; Nada Lokman Mhmmed Ameen AL (University of Mosul-college of Basic Education, 2011)
The current research aims to reveal the effect of using question method on developing Islamic concepts by third Primary female pupils .The researcher used experimental design of two equivalent groups, one is experimental and the other is control. The sample consisted of ( 54 ) pupils falling in to ( 28 ) pupils in the experimental group which was resembles class ( A ) and ( 26 ) pupils in the controh group representing class ( B ) . The researcher made a test of Islamic concepts formed out of ( 25 ) items of Islamic Concepts test that was reliable and stable .The data were dealt with using T.test for two independent grups and Pearson Corelation factor .The results , show few statistically signifieant differences between both ( exper imental & control ) groups regarding pre - and Post tests for developing Islamic concepts in favor of The experimental group . Given the aformentioned results ,anumber of recommendations and suggestion were reached at , one of which is : the necessity of Islamic education teachers to raise questions , inside classroom for its impact in provoking pupils motivation and increase their Coneentration degrees towords learning . The suggestions were : to conduct a study a bout the effect of using interrogation method on the achievement of third year intermediate students in Islamic Education and developing their inclination towards it .